Pendugaan biomassa dan potensi karbon terikat di atas permukaan tanah pada hutan rawa gambut bekas terbakar di Sumatera Selatan - Nong Ayu Eka Widyasari; Bambang Hero Saharjo; . Solichin; . Istomo (Institut Pertanian Bogor, 2010)
Forest has an important role to absorb C02 which is used during photosynthesis to produce 02 and energy. Carbon was stored dominantly in biomass. When peat forest burnt, a lot of carbon emissions are acumulated in the atmosphere, which stimulate global warming. This study aims to estimate biomass and fix carbon contain in ex-burned merang peat forest and make models between biomass and fix carbon of various tree component (stems, branches, twigs and leaves) and also to calculate fix carbon and biomass stock in burned merang peat forest. The results show that biomass and fix carbon in burned merang peat forest can be estimated using allometric equation models: Wtotal = 0.153108 D2,40 and Ctotal = 0,0302 D2,35• Fix carbon stock in the trees very related to biomass and it can be calculated using formula Ctotal = 0.188799 W0,980• Stems store largest proportion of biomass in a single tree. They contribute to approximately 68.09 - 82.28% of total tree biomass. Leaves, twigs and brunch each contribute to 4.17 - 14.44%; 6.16 - 10.32% and 7.15 - 7.45 respectively. Fix carbon of trees can be estimated using biomass formula. It shows that each tree shares 16.49 - 17.70°/o of carbon from total biomass in average. Total biomass and fix carbon on the above ground of burned Merang peat forest are 151,650.48 kg/ha and 29,105.19 kg/ha respectively.